VD_FINDINFO HC / 2014 / 382 vom 12. Mai 2014 - VD Tribunal cantonal (2014)
RELIEF, CODE DE PROCÉDURE CIVILE CANTONAL, RESTITUTION DU DÉLAI | 153 al. 1 CPC, 309 CPC, 310a CPC, 311 CPC, 36 CPC, 318 al. 1 let. c CPC (CH), 405 al. 1 CPC (CH)